Disjunction and Vicariance Between East and West Asia: A Case Study on Euonymus sect. Uniloculares Based on Plastid Genome Analysis - Jamshed, Shayan; Kim, Joo-Hwan (Frontiers in Plant Science, 2022)
Scientists have long been captivated by biogeographic disjunctions, and disjunctions between East Asia and North America have been particularly well-studied at the genus and family levels. By contrast, disjunctions between eastern and western Asia have received less attention. Euonymus L. is taxonomically divided into two sections based on the number of cells in anthers as follows: E. sect. Uniloculares has one-celled anthers and occurs mainly in Asia, whereas E. sect. Biloculares has two-celled anthers and is distributed globally. We used Illumina sequencing to investigate the genomes of four species in sect. Uniloculares. The chloroplast (cp) genomes are highly conserved (157,290–158,094 bp). Pseudogenisation of ndhF and intron loss in rps16 was detected. Based on the cp genomes of the four species of E. sect. Uniloculares, we propose a novel hypothesis of disjunction between eastern and western Asia. Biogeographic reconstruction and molecular dating revealed that sect. Uniloculares separated from its sect. Biloculares forebears 4.0 Mya during the Pliocene era. The radial diversification of sect. Uniloculares from East Asia and the establishment of the western Asian clade during the Pleistocene era (1.9 Mya) were the results of both dispersal and vicariance, making the section the youngest diverged clade conforming to age estimation. The centre of origin of sect. Uniloculares was determined to be in East Asia. Disjunctions and diversification between eastern and western Asia in sect. Uniloculares are thought to have been caused by changes in monsoon patterns, temperature variations, and the emergence of the Gobi Desert.